Signaling in the Physiology and Pathophysiology of Pancreatic Stellate Cells – a Brief Review of Recent Advances - Kusiak, Agnieszka A.; Szopa, Mateusz D.; Jakubowska, Monika A.; Ferdek, Pawel E. (Frontiers in Physiology, 2020)
The interest in pancreatic stellate cells (PSCs) has been steadily growing over the past two decades due mainly to the central role these cells have in the desmoplastic reaction associated with diseases of the pancreas, such as pancreatitis or pancreatic cancer. In recent years, the scientific community has devoted substantial efforts to understanding the signaling pathways that govern PSC activation and interactions with neoplastic cells. This mini review aims to summarize some very recent findings on signaling in PSCs and highlight their impact to the field.